2012
DOI: 10.1007/s10585-012-9476-2
|View full text |Cite
|
Sign up to set email alerts
|

CCL27–CCR10 and CXCL12–CXCR4 chemokine ligand-receptor mRNA expression ratio: new predictive factors of tumor progression in cutaneous malignant melanoma

Abstract: CXCR4, CCR7 and CCR10 chemokine receptors are known to be involved in melanoma metastasis. Our goal was to compare the relative intratumoral mRNA expression of these receptors with that of their corresponding chemokine ligands, CXCL12, CCL19, CCL21, and CCL27 across the full spectrum of human melanoma progression: thin and thick primary melanomas, as well as "in transit", lymph node, and distant metastases. Expression was quantified by real-time RT-PCR in 103 melanoma samples: 51 primary tumors and 52 metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…CXCR4 and CXCR7 have been reported to be higher in ARMS than in ERMS [21,27]; in agreement with this, in the present study we found significant lower CXCL12/CXCR7, CXCL11/ CXCR7 and CXCL12/CXCR4 ratios in ARMS than in ERMS xenografts. These results are equivalent to those reported in melanoma by Monteagudo et al [31] that found the lower ratio values in the most metastatic melanomas. In the same way, we found a significantly higher CXCL12/ CXCR4 ratio in primary ERMS than in their recurrences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…CXCR4 and CXCR7 have been reported to be higher in ARMS than in ERMS [21,27]; in agreement with this, in the present study we found significant lower CXCL12/CXCR7, CXCL11/ CXCR7 and CXCL12/CXCR4 ratios in ARMS than in ERMS xenografts. These results are equivalent to those reported in melanoma by Monteagudo et al [31] that found the lower ratio values in the most metastatic melanomas. In the same way, we found a significantly higher CXCL12/ CXCR4 ratio in primary ERMS than in their recurrences.…”
Section: Discussionsupporting
confidence: 91%
“…The chemokine ligand/receptor ratio has evidenced to be an excellent method for assessing chemokines available in a given tissue. In addition, this method is independent of the housekeeping gene selected for normalization, what contributes to a better standardization of the results [31,41]. CXCR4 and CXCR7 have been reported to be higher in ARMS than in ERMS [21,27]; in agreement with this, in the present study we found significant lower CXCL12/CXCR7, CXCL11/ CXCR7 and CXCL12/CXCR4 ratios in ARMS than in ERMS xenografts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recently, immunohistochemical expression of CXCR4, CCR7 and CCR10 and their ligands has been described in tumor cells from primary and metastatic melanomas. The CXCL12-CXCR4 and CCL27-CCR10 ratios quantified by real time RT-PCR were found to be significantly higher in thin than in thick primary melanomas, and inversely associated with the development of distant metastasis [23]. Although these studies demonstrate the production of chemokines by the tumor cells they do not necessarily indicate their secretion from the cell.…”
Section: Discussionmentioning
confidence: 99%